Hospital performance in Brazil : the search for excellence - La Forgia, Gerard M. (Gerard Martin) (World Bank e-Library., 2008)
Drawing on an eclectic array of research and evaluative studies culled from a mix of sources, this volume analyzes Brazilian hospital performance along several policy dimensions including resource allocation and use within hospitals, hospital payment mechanisms, organizational and governance arrangements, management practices, and regulation and quality. An agenda for hospital reform is proposed which synthesizes priorities that are integral to improving hospital performance?and which should be considered for implementation in the near and medium term.